Imaging Constructs: The Rise of Iron Oxide Nanoparticles - Crețu, Bianca Elena-Beatrice (Molecules, 2021)
Over the last decade, an important challenge in nanomedicine imaging has been the work to design multifunctional agents that can be detected by single and/or multimodal techniques. Among the broad spectrum of nanoscale materials being investigated for imaging use, iron oxide nanoparticles have gained significant attention due to their intrinsic magnetic properties, low toxicity, large magnetic moments, superparamagnetic behaviour and large surface area—the latter being a particular advantage in its conjunction with specific moieties, dye molecules, and imaging probes. Tracers-based nanoparticles are promising candidates, since they combine synergistic advantages for non-invasive, highly sensitive, high-resolution, and quantitative imaging on different modalities. This study represents an overview of current advancements in magnetic materials with clinical potential that will hopefully provide an effective system for diagnosis in the near future. Further exploration is still needed to reveal their potential as promising candidates from simple functionalization of metal oxide nanomaterials up to medical imaging.